The Psychometric Properties of Mindfulness Inventory in Sport and Examination of Its Measurement Invariance - Baykose, Nazmi (2021)
This study aimed to examine the psychometric properties and measurement invariance by testing the validity and reliability of the Turkish form of the "mindfulness inventory in sport, which was developed by Thienot et al. in 2014. Three different data sets were used in the study. Participants for the first data set consisted of 190 athletes (meanage=21,37 ± 2,74), 93 women, and 97 men. The second data set consists of 258 athletes (meanage=21,49 ± 2,76), 128 women and 130 men. Mindfulness Inventory in Sports is a 15-item measurement tool with three sub-dimensions (awareness, non-judgmental, refocusing), the first consists of 5 items, the second 5 items, and the third 5 items. Conscious Awareness Inventory in Sports has been developed to measure the conscious awareness levels of athletes. To examine the psychometric properties of the inventory, the first data set obtained with the participation of 190 athletes was used for reliability and EFA in the context of the construct validity study. The second data set obtained with the participation of 258 athletes was used in the CFA and multi-group confirmatory factor analysis process. The test-retest analysis was conducted with 40 athletes who were included in the research process independently from these two groups. Data analysis was done with SPSS and AMOS package programs. When the AFA results were examined, it was observed that there was no change in the original structure developed by Thienot et al. In the item analysis, it was concluded that all items were above .30, and the representation power of the inventory was sufficient. Besides, Cronbach's alpha internal consistency and test-retest methods were used to demonstrate the inventory's reliability. The study's findings showed that the Mindfulness Scale in Sports is valid and reliable in the Turkish athlete sample.